Earning Per Share, Dividend Per Share, dan Holding Period Saham - Putri, Putu Dinda Sulistia; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 33 No 9 (2023), 2023)
This research aims to determine the effect of earnings per share on the holding period of shares with dividend per share as a moderating variable. The population in this study are companies registered in IDX30 for the 2016-2019 period. The sampling technique in the research used the purposive sampling method. Simple linear regression is used to determine the effect of earnings per share, while moderated regression analysis is used to determine the effect of the moderating variable. The research results show that earnings per share have a positive effect on the holding period of shares, while dividends per share are unable to moderate the effect of earnings per share on the holding period. The theoretical implications of the research are able to support signaling theory as well as the practical implications of the research as consideration for companies to improve financial performance and decisions to retain share ownership by investors. Keywords: holding period; earning per share; dividend per share